2010
DOI: 10.3109/09513590.2010.521268
|View full text |Cite
|
Sign up to set email alerts
|

Successful outcome of pregnancy in a patient with Cushing's disease under treatment with ketoconazole during the first trimester of gestation

Abstract: Treatment with ketoconazole during the critical period of organogenesis did not cause congenital birth defects to the male fetus of a woman with Cushing's disease. This report should be taken into account for future cases of unplanned pregnancies in women with Cushing's syndrome treated with ketoconazole, as well in those cases in which other therapeutic options are not feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Women on medical therapy for CS may also become pregnant or women may relapse during pregnancy (124,125). Medical or surgical treatment has complications but so does uncontrolled hypercortisolism, and treatment should be individualised, taking into account the gestational age of the pregnancy.…”
Section: Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Women on medical therapy for CS may also become pregnant or women may relapse during pregnancy (124,125). Medical or surgical treatment has complications but so does uncontrolled hypercortisolism, and treatment should be individualised, taking into account the gestational age of the pregnancy.…”
Section: Pregnancymentioning
confidence: 99%
“…Amado et al (136) reported the use of KTZ in the 3rd trimester in a 36-year-old woman with CS due to an adrenocortical adenoma; doses up to 600 mg daily were given between 32 and 37-week gestation of a female foetus, resulting in a significant reduction in UFC and no maternal or neonatal complications. There have been reports of uncomplicated pregnancies and live births of healthy male babies in women who were treated with KTZ at conception and throughout the first trimester (124,125).…”
Section: Pregnancymentioning
confidence: 99%
“…Although it crosses the placental membrane in animal studies, no neonatal abnormalities have been reported in human patients (28,29). Ketoconazole, the steroidogenesis inhibitor used most often in non-pregnant CS patients, has been utilized less during pregnancy because of its potential side effects, which include an anti-androgenic effect and teratogenicity (only shown in animal studies) (17,30,31). Other adrenal steroidogenesis blockers, such as aminoglutethimide and mitotane, were rarely used, because they were contraindicated as a result of fetal masculinization and teratogenicity respectively (16).…”
Section: Treatment Of Pregnancies With Csmentioning
confidence: 99%
“…In two of the four cases ketoconazole was used during the first trimester of pregnancy. [7][8][9][10] In the rat, ketoconazole crosses the placenta and is teratogenic, and in humans it is classified as FDA category C. A recent population-based case-control study did not find a higher rate of congenital abnormalities in infants born to mothers who had received oral ketoconazole treatment during pregnancy; however, the number of exposed cases and controls was too small to allow for solid conclusions. 11 Moreover, ketoconazole has antiandrogenic effects through inhibition of aromatase activity.…”
Section: Discussionmentioning
confidence: 99%